PKM Pelatihan Tari Kreasi pada Siswa-Siswi Kelas 2 SMA Negeri 8 Gowa - Nurlina Syahrir; Johar Linda; Rahma Rahma (DEDIKASI, 2020)
The ability of second grade students of SMA NEGERI 8 GOWA in dance lessons, especially creative dance, is still below standard. This is ofcourse an obstacle in demonstrating these creative dances, and also an obstacle in the development of regional creation dances.Therefore, a creative dance training was held for the 2nd grade students of SMA NEGERI 8 GOWA. the implementation of the training aims to improve the skills and knowledge of students in demonstrating creative dances, especially the Pa’duppa dance. Creative dance training uses the method of lecturing on theory and demonstration in practice, while the steps taken are: 1. The preparatory stage includes site observation; a. Site observation, b. Processing permission letter, c. Determine the training schedule, 2. Implementation includes, a. Provides material theory / introduction to creative dance, b. Giving practice material, c. Evaluation. Training is carried out to cover the shortcomings, weaknesses, and demands of an institution or school, due to the lack of talent and interest of students in the field of dance, if there are talented people, most of them are below standartd. After the implementation of creative dance training, students are expected to be able to demonstrate and develope and create dances that have been taught and make a traditional culture to be proud of. However, it should be noted that each ethnic group in South Sulawesi has a different cultural background, which in the development of traditional culture, it is necessary to pay attention to these differences, so as not to become a misunderstanding.